Klauzula dotycząca zatrudnienia z art. 29 ust. 3a Prawa zamówień publicznych z perspektywy art. 7 Międzynarodowego Paktu Praw Gospodarczych, Społecznych i Kulturalnych - Lubiszewski, Maciej (Studia Prawnoustrojowe, 2019)
This contribution provides an analysis of the labour clause (article 29.3a of the Public Procurement Law) from the perspective of the right to just and favourable conditions of work as guaranteed in Article 7 of International Covenant on Economic, Social and Cultural Rights. This analysis indicates that the labour clause, in addition to the implementation of the EU procurement directives, also fulfils Poland’s obligations under Article 7 of the Covenant. This fulfilment occurs in a full spectrum of the triad of duties, i.e. in the sphere of the obligation to respect, protect and fulfil the right to fair and favourable working conditions. It was also concluded that, from the national point of view, contracting authorities and contractors can be considered to be obliged entities bound by the international law of human rights (although without the international legal personality) if their acts can be attributed to the state.